First Aspect of Conventional Power System Assessment for High Wind Power Plants Penetration - A Merzic; M. Music; M Rascic (Center of Biomass & Renewable Energy, Diponegoro University, 2012)
Most power systems in underdeveloped and developing countries are based on conventional power plants, mainly